Relationship Between Linear Running and Change of Direction Performances of Male Soccer Players - Armağan Şahin Kafkas; Fahri Safa Çınarlı; Muhammed Emin Kafkas (Türk Spor ve Egzersiz Dergisi)
It is known that there is a strong correlation between performance and match performance in terms of soccer players. Furthermore, it is expressed that the agility and the linear sprint have different performance skills. Therefore, the purpose of this study was to analyze the relationship between linear sprint and change in performance scores and determine the most appropriate agility test for soccer players. 16 male soccer players (age: 21.93 ± 3.62 years, height: 175.06 ± 3.06 cm, body mass: 69.51 ± 7.40 kg, body mass index: 22.67 ± 2.16 kg / m 2, body fat ratio: 7.52 ± 2.64% linear sprint and agility tests. All participants completed a test battery involving linear sprinting (10, 20, 30 m), agility tests (T test, 505, Pro-agility, illinois). The 10, 20, and 30 m sprint performance were positively correlated with the illinois agility test (p lt;0.05). Furthermore, the 20-m sprint performance was positively correlated (r = .571, p = .042) with performance on pro-agility test. (R = .329, p = .272; r = .370, p = .214; r = .338, p = .259 respectively) with performance on T test but this correlation levels were not significance. Given these meaningless relationships, it may state that the most appropriate agility tests are T test for soccer players.